2016
DOI: 10.1080/09638288.2016.1236155
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapist-delivered cognitive-behavioural interventions are effective for low back pain, but can they be replicated in clinical practice? A systematic review

Abstract: With additional training, physiotherapists can deliver effective CB interventions. However, without training or resources, successful translation and implementation remains unlikely. Researchers should improve reporting of procedural information, provide relevant materials, and offer accessible provider training. Implications for Rehabilitation Previous reviews have established that traditional biomedical-based treatments (e.g., acupuncture, manual therapy, massage, and specific exercise programmes) that focus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
112
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(120 citation statements)
references
References 25 publications
6
112
0
2
Order By: Relevance
“…It is important to select therapists based on their BPS skills or to adequately educate and support them in providing BPS elements. The essential role of sufficient training and resources (eg, treatment protocols and support) in complex behavioral interventions can be confirmed by the current literature . Both studies suggest that if physiotherapists receive appropriate training and resources, and possess sufficient competencies, physiotherapists will be able to effectively provide a cognitive‐behavioral intervention.…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…It is important to select therapists based on their BPS skills or to adequately educate and support them in providing BPS elements. The essential role of sufficient training and resources (eg, treatment protocols and support) in complex behavioral interventions can be confirmed by the current literature . Both studies suggest that if physiotherapists receive appropriate training and resources, and possess sufficient competencies, physiotherapists will be able to effectively provide a cognitive‐behavioral intervention.…”
Section: Discussionmentioning
confidence: 58%
“…Compared with physical treatments, Kamper et al found low‐quality evidence for greater effectiveness of behavioral treatments, and Henschke et al moderate‐quality evidence. Hall et al even reported high‐quality evidence for greater effectiveness of BPS interventions compared with exercise interventions. Our systematic review did not detect a difference between a BPS intervention and physical activity therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Combining PT and cognitive behavioral therapy improves functioning in children experiencing pain (Ayling Campos, Amaria, Campbell, and McGrath, 2011;Lee et al, 2002;Sherry et al, 1999). Physical therapist delivered cognitive-behavioral interventions are more effective than other guideline based treatments (Hall et al, 2018).…”
Section: Introductionmentioning
confidence: 99%